Are Orthopedic Fellowship Programs Giving Out Too Many Interviews? A Retrospective Analysis Suggests They Are. Issue 2 (May 2023) - Sutton, Ryan; Wang, William L.; Abdelfadeel, Walaa; Sherman, Matthew; Cannada, Lisa K.; Krueger, Chad A.
Background: The orthopedic surgery fellowship match process is associated with substantial stress and expense, yet the optimal number of interviews for fellowships to offer has not been evaluated. Purpose : We sought to evaluate the number of orthopedic surgery fellowship interviews given and construct a model to determine the appropriate number of interviews to offer based on specialty and program size. Methods : We conducted a retrospective study of 6 orthopedic fellowship specialties; data were obtained from San Francisco Match and covered the 5-year period from 2014 to 2018. The orthopedic fellowship subspecialties included adult reconstruction/oncology, foot and ankle, pediatrics, spine, sports medicine, and trauma. We excluded shoulder and elbow (less than 5 years of data) and hand and upper extremity (alternative matching process). Parameters included number of programs, number of spots per program, number of ranked applicants per program (mean ± SD), and difference in number of interviews offered and ranked applicants per program (mean ± SD). Multiple regression analysis was used to create an equation for determining the optimal number of interviews for the programs. Results : Of 1377 orthopedic fellowship programs analyzed, 1370 (99.50%) conducted interviews beyond the number of ranked applicants. Programs ranked an overall mean of 20.10 ± 10.17 applicants with an overall mean of 11.60 ± 8.62 additional interviews offered. Sports medicine had the highest mean ranked applicants (23.21 ± 9.77) and pediatrics had the lowest mean ranked applicants (15.74 ± 7.76). The most additional interviews were given in adult reconstruction (14.80 ± 9.92) and the least were given in pediatrics (8.32 ± 7.17). The predictive equation was reported as Y = β1 x1 + β2 x2 (Y = ranked applicants, x1 = spots open, and x2 = last rank). Conclusion : Programs in 6 orthopedic subspecialties in the fellowship match process appear to consistently offer more interviews than necessary. We have developed a model to help programs predict the optimal number of fellowship applicants to interview. Future studies need to validate the model, especially with anticipated increases of the virtual interview format.